How many individuals will need to be screened to increase colorectal cancer screening prevalence to 80% by 2018?. Issue 23 (26th August 2015) - Fedewa, Stacey A.; Ma, Jiemin; Sauer, Ann Goding; Siegel, Rebecca L.; Smith, Robert A.; Wender, Richard C.; Doroshenk, Mary K.; Brawley, Otis W.; Ward, Elizabeth M.; Jemal, Ahmedin
Abstract : BACKGROUND: A recent study estimates that 277, 000 colorectal cancer (CRC) cases and 203, 000 CRC deaths will be averted between 2013 and 2030 if the National Colorectal Cancer Roundtable goal of increasing CRC screening prevalence to 80% by 2018 is reached. However, the number of individuals who need to be screened (NNS) to achieve this goal is unknown. In this communication, the authors estimate the NNS to achieve 80% by 2018 nationwide and by state. METHODS: The authors estimated the NNS by subtracting adults aged 50 to 75 years who would need to be screened to achieve an 80% CRC screening prevalence from the number who are currently guideline‐compliant from population estimates for this age group. The 2013 National Health Interview Survey and the 2012 Behavioral Risk Factor Surveillance System were used to estimate CRC screening prevalence and data from the US Census Bureau were used to estimate population projections. The NNS were age‐standardized and sex‐standardized. RESULTS: Nationwide, 24.39 million individuals (95% confidence interval, 24.37‐24.41 million) aged 50 to 75 years will need to be screened to achieve 80% by 2018. By state, the NNS ranged from 45, 400 in Vermont to 2.72 million in California. The majority of individuals who need to be screened are aged 50 to 64 years and the largest subgroup is privately insured. CONCLUSIONS: The authors estimated that at least 24.4 million additional individuals in the United States will need to be screened to achieve the National Colorectal Cancer Roundtable goal of increasing CRC screening prevalence to 80% by 2018. To reach this goal, improving facilitators of CRC screening, including physician recommendation and patient awareness, is needed. Cancer 2015;121:4258–4265. © 2015 American Cancer Society . Abstract : In the current study, the authors estimate that 24.4 million individuals in the United States will need to be screened to achieve the National Colorectal Cancer Roundtable goal of increasing colorectal cancer screening prevalence to 80% by 2018. To reach this goal, increasing known facilitators of colorectal cancer screening, including physician recommendation, access to care, and patient awareness, is needed.